Numerical simulations of transient flows in shock tube and validations with experimental measurements - Yusoff M.Z.; Al-Falahi A.; Shuaib N.H.; Yusaf T. (EUROSIS, 2023)
This paper describes the numerical simulations of transient flows in shock tube which involves multiple reflections of shockwaves, contact surface and expansion waves and their interactions. The numerical formulations solve the fully compressible Reynolds Averaged Navicr Stokes (RANS) equations set using finite volume method. The numerical results are validated against analytical solutions and experimental measurements in the high speed flow test facility available at the Universiti Tenaga Nasional (UNITEN), Malaysia. Experimental tests for different operating conditions have been performed. High precision pressure transducers were used to measure the pressure history at two different locations within the shock tube. Experimental results were compared with the numerical results and good agreements were obtained. The numerical simulations also revealed that the flow tend to be very unstable in the region close to the diaphragm after the reflected shock wave interacts with the contact surface. 2008 EUROSIS-ETI.